The Civil Juridical Act - Petru Tărchilă (Journal of Humanistic and Social Studies, 2014)
The legislative act is the subjects’ will to create, modify or extinguish a juridical relation of Civil Law. Hence the fundamental elements of the existence of civil juridical act, namely: - the subjects’ manifestation of will, - intention to produce civil juridical relations, - the juridical effects whose induction is aimed by parties. Consent is an essential prerequisite of validity for any juridical act and it is defined as the parties’ decision to complete the juridical act. The consent must meet the following conditions to acquire legal value, to be considered valid: - to be issued by a judicial person, - to be externalized, - to have the intention of producing legal effects, - not be affected by any consent flaw: mistake, fraud, violence or damage.